Citrus Polyamines: Structure, Biosynthesis, and Physiological Functions - Killiny, Nabil (Plants (Basel), 2020)
Polyamines (PAs) are ubiquitous biogenic amines found in all living organisms from bacteria to Archaea, and Eukaryotes including plants and animals. Since the first description of putrescine conjugate, feruloyl-putrescine (originally called subaphylline), from grapefruit leaves and juice, many research studies have highlighted the importance of PAs in growth, development, and other physiological processes in citrus plants. PAs appear to be involved in a wide range of physiological processes in citrus plants; however, their exact roles are not fully understood. Accordingly, in the present review, we discuss the biosynthesis of PAs in citrus plants, with an emphasis on the recent advances in identifying and characterizing PAs-biosynthetic genes and other upstream regulatory genes involved in transcriptional regulation of PAs metabolism. In addition, we will discuss the recent metabolic, genetic, and molecular evidence illustrating the roles of PAs metabolism in citrus physiology including somatic embryogenesis; root system formation, morphology, and architecture; plant growth and shoot system architecture; inflorescence, flowering, and flowering-associated events; fruit set, development, and quality; stomatal closure and gas-exchange; and chlorophyll fluorescence and photosynthesis. We believe that the molecular and biochemical understanding of PAs metabolism and their physiological roles in citrus plants will help citrus breeding programs to enhance tolerance to biotic and abiotic stresses and provide bases for further research into potential applications.